Analytical Computation of the Three-Dimensional Steady-State Temperature Condition of a Dam (Ob Analiticheskom Raschete Prostranstvennogo Statsionarnogo Temperaturnogo Sostoyaniya Plotiny) - Bogoslovskiy,P A (1977)
Temperature conditions are of very great significance for earth dams based on permafrost ground. One of the indices of the temperature condition of non-filtering earth dams on a permafrost base is the steady-state (temporally invariable) temperature distribution for mean annual conditions, that is, for the mean water level in the reservoir, and the mean temperature readings at ground level. Tasks such as these have been reviewed for two-dimensional conditions on the assumption of a very broad river valley as compared with the cross-sectional dimensions of the dam. But consideration also must be given to three-dimensional conditions, where dams abut the sides of valleys, for example, in order to evaluate the cooling influence of the sides of a valley, and other factors, in order to solve engineering problems. These questions ordinarily are elucidated by electrothermal analogy testing of models. These factors are the reason for seeking an analytical solution to the three-dimensional problems of the steady-state temperature field. (Author) Trans. of Sbornik Trudov po Gidrotekhnike i Gidrostroitel'stva pri Stroitel'stve Plotin v Surovykh Klimaticheskikh Usloviyakh (USSR) p24-30 1970.